Gender Equality in Islamic Marriage Law through the Maqāṣid al-Sharī’a Perspective: A Study on Woman-initiated Divorce (Cerai Gugat) in Indonesia - Mufti, Muhammad (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2024)
The presence of gender equality issues in Islamic family law has already become a new challenge faced by Muslims to manifest and uphold the higher purpose of sharī’a (maqāṣid al-sharī’a). Thus, maqāṣid al-sharī’a as a theoretical framework should be able to accept adjustment depending on the circumstance. This article aims to discuss the notion of gender equality in maqāṣid al-sharī’ah perspective, which is focused on two research questions, namely what is the perspective of maqāṣid al-sharī’a on gender equality discourse, especially in Islamic marriage law, and how can the reform of Islamic marriage law in the practice of divorce support the realization of a new paradigm of maqāṣid al-sharī’a to achieve justice. Using woman-initiated divorce (cerai gugat) in recent Indonesia as a case study and incorporating a normative legal approach along with the Islamic feminism theory proposed by Amina Wadud, the article concludes that the maqāṣid al-sharī’a applied in the Muslim legal tradition demonstrates the flexibility of Islamic law in adapting to various demands and circumstances. In the context of Islamic family law in Indonesia, it can be proven by the presence of woman-initiated divorce (cerai gugat) which has never been done before. It became a manifestation of the ability of maqāṣid al-sharī’a to reconcile contemporary issues such as the notion of gender equality.